MEDIASI KELUARGA DALAM KRISIS: ANALISIS RENDAHNYA KESADARAN PUBLIK TERHADAP BP4 DALAM SISTEM PENYELESAIAN SENGKETA PERKAWINAN DI INDONESIA - Rahmatullah, Reza; Muhammad, Fauzi; Mursalin, Ayub (TAHKIM, 2025)
This study aims to critically examine the low utilization of the Marriage Advisory, Guidance, and Preservation Agency (BP4) as a family mediation institution for resolving domestic conflicts in Indonesia. Based on a review of literature, regulatory documents, and previous research findings, it is known that BP4 has not been functioning optimally due to various structural, normative, and cultural factors. The results indicate that limited human resource capacity, inadequate budget and operational facilities, and low professionalism of mediators are the main obstacles in implementing BP4's mediation function. Furthermore, BP4's lack of integration with the formal legal system and the absence of regulations mandating pre-suit mediation have caused this institution to lose its legitimacy and strategic role. Negative public perceptions of the effectiveness of BP4 mediation also exacerbate low participation in this service. Using a theoretical approach based on legal awareness and conflict resolution, this study emphasizes the need for institutional reform of BP4, including strengthening regulations, training certified mediators, digitizing services, and increasing public trust. Comprehensive reform of this area is essential so that the BP4 can effectively carry out its preventive and resolutive functions in preventing divorce and strengthening family institutions in Indonesia. Keywords: BP4, family mediation, divorce, dispute resolution